ESG Performance during Financial Performance and Reporting Quality Shortfalls: Proving Signaling Theory in Indonesia - Firdaus Kurniawan; Albertus Henri Listyanto Nugroho (Universitas Hayam Wuruk Perbanas, 2025)
This study aims to examine the inverse relationship between financial performance shortfalls and corporate ESG performance to determine whether companies exploit biases that can be created by using corporate ESG performance as a signaling mechanism. The sample of this study consists of companies listed on the Indonesia Stock Exchange from 2000 to 2023. The final sample includes 450 company-year observations. The results of this study indicate that there is a negative correlation between the decline in short-term financial performance and the company's ESG performance. In addition, corporate stakeholders in developing countries, such as Indonesia, still lack confidence and trust in company’s environmental, social, and governance (ESG) strategies, which contributes to the less effective performance of ESG as a signaling mechanism for companies in Indonesia. In addition to contributing to investor decision-making processes focused on issues related to corporate environmental and social sustainability, the results of this study are also expected to help investors and regulators understand environmental, social, and governance (ESG) activity patterns when companies face financial performance shortfalls. Finally, this study provides theoretical validation of signaling theory in the context of developing countries, specifically Indonesia.